Waqf Transformation: Public Investment Opportunities for Sustainable Development - Intan, Intan Farrel Aurellia; Indrasari , Widya; Fitriani Putri, Azzahra (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2023)
This Islamic philanthropic concept has undergone a significant transformation, adapting to the dynamics of modern society, changing the concepts of the wakaf from simple to complex socio-economic instruments, in line with the economic and technological dynamics. The objective of the research is to identify the role of waqf in addressing social and economic challenges, as well as to evaluate its positive impact on sustainable development, also to investigate the development of waqf in the context of modern society undergoing significant transformation. The research method used is library research, by conducting a general review of previously published literary works on a wide range of topics. The Islamic financial institutions provide financial products in accordance with the Shariah, facilitating the efficient management of the Wakaf. Technology, in particular blockchain, provides transparency in waqf asset management. Productive Wakaf and innovative projects such as higher education centres or hospitals support sustainable development. This research provides insight into the evolution of waqf as a public investment instrument with a positive impact on economic growth and society's well-being. The Wakaf transformation reflects a strategic effort to optimally utilize the funds to the goals of sustainable development in the context of modern society.